Impact of Logistics Factors on Procurement of Construction Materials in Lokoja, Kogi State - Ohida, Muhammed Etudaiye; Imam, Isa; Ajiboye, Araoye Olarinkoye (UI Scholars Hub, 2024)
This study investigates the influence of logistics factors on the procurement of construction materials in Lokoja, Kogi State, aiming to identify and rank the critical elements affecting material procurement in building projects. A total of 250 questionnaires were distributed across nineteen neighborhoods in Lokoja using a random sampling technique. Data were analyzed using descriptive statistics, while the T-test assessed the significance of identified logistics factors. The findings revealed that seventeen logistics factors influence material procurement, with seven factors emerging as the most significant: on-time delivery, transportation challenges, material misdelivery, delivery inaccuracies, order processing, storage capacity limitations, and ineffective information flow. These factors were ranked by their impact on procurement processes, with hypothesis testing confirming a statistically significant relationship between logistics factors and material procurement efficiency. The study concludes that effective management of key logistics factors is essential to avoid cost overruns, delays, and material wastage. It recommends that project managers prioritize better coordination among stakeholders to address logistics-related challenges, ensuring materials are delivered efficiently and on time.